Hydrochemical Characterization and Water Quality of Perennial Rivulets (Darchula), Sudurpashchim Province, Nepal - Bohara, Rupesh; Sitaula, Sagar; Basnet, Niru; Awasthi, Mahesh Prasad; Rawal, Sabin; Joshi, Tark Raj; Byanju, Rejina Maskey; Pant, Ramesh Raj (Tribhuvan University Journal, 2024)
Available with Fulltext.